Transmission of Hepatitis B Virus in Dialysis Units: A Systematic Review of Reports on Outbreaks. Issue 1 (January 2015) - Fabrizi, Fabrizio; Dixit, Vivek; Messa, Piergiorgio; Martin, Paul
Background: Changes in the delivery of healthcare in the developed world have resulted in frequent reporting of outbreaks of hepatitis B virus (HBV) infection in nonhospital healthcare settings, including hemodialysis units. Aim: We performed a systematic review of HBV outbreaks in dialysis units of developed and less-developed countries published between 1992 and 2014 to elucidate the most frequent mechanisms of patient-to-patient transmission of HBV in this setting. Methods: The research was performed using the PubMed Database and the Outbreak Database; studies were selected according to the PRISMA algorithm. Inclusion criteria were established before the papers were retrieved in order to avoid selection biases. Results: 12 papers reported on 16 outbreaks that involved 118 patients on maintenance dialysis; 10 fatal cases occurred. European outbreaks were smaller compared with the others (P = 0.0046). Information on specific transmission pathways was given in many outbreaks (n = 10; 62%); multiple deficiencies in standard or hemodialysis-specific procedures was the most common route of patient-to-patient transmission of HBV (80%, 8/10). De novo HBV from HBsAg negative/HBV DNA positive blood donors was found in 2 (20%) oubreaks. Sharing of contaminated HD machines was mentioned in 1 report. Conclusions: Our systematic review of HBV outbreaks shows that incomplete adherence to standard and dialysis-specific infection control precautions was the most important cause of patient-to-patient transmission of HBV in dialysis units. This review should serve as a reminder to HD providers that the risk of HBV infection is still present among patients undergoing dialysis and that HBV may be easily transmitted in the dialysis setting whenever appropriate infection control practices are not strictly applied.